Nbeal2 Deficiency Increases Organ Damage but Does Not Affect Host Defense During Gram-Negative Pneumonia-Derived Sepsis. Issue 8 (August 2018) - Claushuis, Theodora A.M.; de Stoppelaar, Sacha F.; de Vos, Alex F.; Grootemaat, Anita E.; van der Wel, Nicole N.; Roelofs, Joris J.T.H.; Ware, Jerry; van't Veer, Cornelis; van der Poll, Tom
Abstract : Objective—: Nbeal2 −/− mice, a model of human gray platelet syndrome, have reduced neutrophil granularity and impaired host defense against systemic Staphylococcus aureus infection. We here aimed to study the role of Nbeal2 deficiency in both leukocytes and platelets during gram-negative pneumonia and sepsis. Approach and Results—: We studied the role of Nbeal2 in platelets and leukocytes during murine pneumonia and sepsis by Klebsiella pneumoniae . Apart from platelet α-granule deficiency and reduced neutrophil granularity, also monocyte granularity was reduced in Nbeal2 −/− mice, whereas plasma levels of MPO (myeloperoxidase), elastase, NGAL (neutrophil gelatinase–associated lipocalin), and MMP-9 (matrix metalloproteinase 9), and leukocyte CD11b expression were increased. Nbeal2 −/− leukocytes showed unaltered in vitro antibacterial response and phagocytosis capacity against Klebsiella, and unchanged reactive nitrogen species and cytokine production. Also during Klebsiella pneumonia and sepsis, Nbeal2 −/− mice had similar bacterial growth in lung and distant body sites, with enhanced leukocyte migration to the bronchoalveolar space. Despite similar infection-induced inflammation, organ damage was increased in Nbeal2 −/− mice, which was also seen during endotoxemia. Platelet-specific Nbeal2 deficiency did not influence leukocyte functions, indicating that Nbeal2 directly modifies leukocytes. Transfusion of Nbeal2 −/− but not of Nbeal2 +/+ platelets into thrombocytopenic mice was associated with bleeding in the lung but similar host defense, pointing at a role for platelet α-granules in maintaining vascular integrity but not host defense during Klebsiella pneumosepsis. Conclusions—: These data show that Nbeal2 deficiency—resulting in gray platelet syndrome—affects platelets, neutrophils, and monocytes, with intact host defense but increased organ damage during gram-negative pneumosepsis. Abstract : Supplemental Digital Content is available in the text.